The molecular cloning and clarification of a photorespiratory mutant, oscdm1, using enhancer trapping - Wu, jinxia; Zhang, Zhiguo; Zhang, QIan; Han, Xiao; Gu, Xiaofeng; Lu, Tiegang (Frontiers in Genetics, 2015)
Enhancer trap systems have been demonstrated to increase the effectiveness of gene identiﬁcation in rice. In this study, a chlorophyll-deficient mutant, named oscdm1, was screened and characterized in detail from a T-DNA enhancer-tagged population. The oscdm1 plants were different from other chlorophyll-deficient mutants; they produced chlorotic leaves at the third leaf stage, which gradually died with further growth of the plants. However, the oscdm1 plants were able to survive exposure to elevated CO2 levels, similar to photorespiratory mutants. An analysis of the T-DNA flanking sequence in the oscdm1 plants showed that the T-DNA was inserted into the promoter region of a serine hydroxymethyltransferase gene. OsSHMT1 is a key enzyme that is ubiquitous in nature and structurally conserved across kingdoms. The enzyme is responsible for the interconversion of serine and glycine and is essential for cellular one-carbon metabolism. Full-length OsSHMT1 complemented the oscdm1 phenotype, and the downregulation of OsSHMT1 in wild-type plants by RNA interference produced plants that mimicked the oscdm1 phenotype. GUS assays and quantitative PCR revealed the preferential expression of OsSHMT1 in young leaves. TEM revealed serious damage to the thylakoid membrane in oscdm1 chloroplasts. The oscdm1 plants showed more extensive damage than wild type using an IMAGING-PAM fluorometer, especially under high light intensities. OsSHMT1-GFP localized exclusively to mitochondria. Further analysis revealed that the H2O2 content in the oscdm1 plants was twice that in wild type at the fourth leaf stage. This suggests that the thylakoid membrane damage observed in the oscdm1 plants was caused by excessive H2O2. Interestingly, OsSHMT1-overexpressing plants exhibited increased photosynthetic efficiency and improved plant productivity. These results lay the foundation for further study of the OsSHMT1 gene and will help illuminate the functional role of OsSHMT1 in photorespiration in rice.